Amaurosis Fugax associated with the ophthalmic artery stenosis - Nose, Harumi; Nose, Tadao; Yanaka, Kiyoyuki; Maki, Yutaka; Kobayashi, Eiki (Japanese Journal of Stroke, 1989)
Amaurosis fugax is a hallmark of atheroscloerotic disease in the carotid artery. We report 3 cases of amaurosis fugax associated with the ophthalmic artery stenosis. No lesion was evident in the carotid artery, but significnat ophthalmic artery stenosis was identified on the cerebral angiography in these 3 cases. Amaurosis fugax may be caused by a retinal ischemia due to ophthalmic artery stenosis. We discuss the mechanisms of occurrence of Amaurosis Fugax. And further, the concept of small vessel disease related to the cerebral infarction is advocated.